Charles Dickens and the street children of London - Warren, Andrea (Houghton Mifflin Books for Children/Houghton Mifflin Harcourt, 2011)
A biography of Charles Dickens, discussing how his father's debts forced him to go to work in a shoe polish factory, and looking at how his observations of the poor led him to write novels with an eye toward bringing attention to the plight of London's destitute children.